Association between constipation and major depression in adult Americans: evidence from NHANES 2005–2010 - Wang, Pengfei; Shen, Xia; Wang, Yan; Jia, Xiaoqiang (Frontiers in Psychiatry, 2023)
Objective Current studies on the association between constipation and depression is still insufficient. In this study, we investigated the detailed association between constipation and major depression among American adults. Methods In this cross-sectional study, 12,352 adults aged 20 and older were selected from the National Health and Nutrition Examination Survey 2005–2010 for the sample. Constipation was defined as fewer than three defecation frequencies per week. For the assessment of major depression, the validated Patient Health Questionnaire-9 was used. Adjusted odds ratios (ORs) were calculated using multivariate logistic regression models. A subgroup analysis was carried out to ensure that the results were stable. Results Of the 12,352 participants, 430 reported constipation, with a prevalence of 3.5%. Depression was reported in 1030 cases, indicating a prevalence rate of 8.3%. Patients with constipation were significantly more likely to have major depression (20.9%) than those without it (7.9%, p < 0.001). After adjusting for age, sex, race/ethnicity, marital status, education level, body mass index, vigorous physical activity, alcohol consumption, smoking status, poverty income ratio, diabetes, selective serotonin reuptake inhibitor use, liver disease, heart disease, pulmonary disease, hypertension, arthritis, cancer, dietary fiber intake, moisture intake, total fat intake, carbohydrates intake, and protein intake, constipation is significantly associated with major depression (OR: 2.20, 95%CI: 1.68–2.87, p < 0.001). Subgroup analyses by age, sex, dietary intake, risk behaviors, and common complications showed no statistically significant interactions (p > 0.05). Conclusion In conclusion, this study showed that constipation were significantly associated with depression. When treating patients with constipation, it is necessary for clinicians to screen and evaluate depression, and provide timely and effective intervention for patients with depression to avoid further deterioration of the condition.